Early detection of lung cancer based on DNA methylation analysis in sputum and plasma - Lianidou, Evi; Alix-Panabières, Catherine (Translational Cancer Research, 2017)
Lung cancer kills millions of people each year in the world and is the main cause of cancer death in men and the second cause in women (1). Surprisingly, a decade ago, lung cancer was not so frequently diagnosed compared to breast and prostate cancer, explained by the fact that these cancers can be detected at a very early stage. For lung cancer, the five-year survival rate was as low as 15%. However, when lung cancer can be detected at an early stage, the survival rate increases dramatically (2). Using low-dose computed tomography (CT) screening, a 20% reduction in lung cancer mortality has been more recently reported (3). Thus, during this last decade, many efforts have been made to develop innovative technologies to detect lung cancer very early, with a special focus on molecular markers as an alternative approach to different imaging and cytology-based strategies.